Peran Inputer Indikator Kinerja Utama (Iku) Dalam Pengelolaan Data Kinerja Direktorat Perencanaan Strategis Dan Manajemen Kinerja Badan Pemeriksa Keuangan - Anton Siswanto; Ngadisah Ngadisah; Andi Masrich (UIR Press, 2022)
Performance data management is carried out by recording, processing, and reporting performance data. The measurement of performance achievement at BPK is supported by the role of the Key Performance Indicators (KPI) input. Where the KPI input does not meet the level of reliability. The purpose of this study was to find out what factors caused the role of KPI inputers to not fully meet the level of reliability (timeliness of data input, completeness of supporting data and accuracy of supporting data) in the ideal SIMAK/PRISMA data input; and develop strategies to increase the role of KPI inputers in order to increase reliability. This study uses a qualitative research method with a descriptive approach using Soerjono Soekanto's active role theory. Sources of data obtained from primary data and secondary data. The analysis technique uses SWOT analysis. Data collection techniques through interviews, observations and documentation carried out at the Directorate of Strategic Planning and Performance Management. Resource persons as informants in this study are KPI inputers. The results showed that the factors that caused the role of the KPI inputer to not fully meet the ideal level of reliability in inputting SIMAK/PRISMA data were the KPI inputer in carrying out the role of prioritizing the main task, where being a KPI inputer was an additional task; availability of data from parties other than KPI inputers who have not provided data by the time limit; there is limited knowledge of the inputer on the use of the application; the data period required is different from the input period; the existence of human error, the inputer mistakenly saw the numbers and typed them; the data to be input takes time in a tiered review, the work process is still ongoing so that the required data does not yet exist; data/document access restrictions. There are six strategies that can be used to increase the role of KPI inputers, namely maintaining social relations/interrelationships on an ongoing basis in order to cooperate with other parties regarding data input; maximizing the facilities and infrastructure to support the task of inputting data; propose a re-evaluation of data access restrictions; propose to take part in related training for unskilled KPI inputers; proactive in collecting data from various parties.